Exploring American Healthcare through 50 Historic Treasures - Kehoe, Tegan (Rowman & Littlefield Publishers, 2022)
Healthcare history is more than leeches and drilling holes in skulls. It is stories of scientific failures and triumphs. Exploring American Healthcare through 50 Historic Treasures presents a visual and narrative history of health and medicine in the United States, tracing paradigm shifts such as the introduction of anesthesia, the adoption of germ theory, and advances in public health. In this book, museum artifacts are windows into both famous and ordinary people’s experiences with healthcare throughout American history, from patent medicines and faith healing to laboratory science. With 50 vignette-like chapters and 50 color photographs, Exploring American Healthcare through 50 Historic Treasures showcases little-known objects that illustrate the complexities of our relationship with health, such as a bottle from the short period when the Schlitz beer company sold lager that was supposed to be high in vitamin D during the first vitamin craze. It also highlights famous moments in medicine, such as the discovery of penicillin, as illustrated by a mold-culturing pan. Each artifact tells some piece of the story of how its creators or users approached fundamental questions in health. Some of these questions are, “What causes sickness, and what causes health?” and “How much can everyone master the principles of health, and how much do laypeople need to rely on outside authorities?” Exploring American Healthcare through 50 Historic Treasures describes the days when surgeons worked on patients without anesthesia and wiped their scalpels on their coats, and the day that EMTs raced to provide help when the Twin Towers were attacked in 2001. The book discusses social and cultural influences that have shaped healthcare, providing insight relevant to today’s problems and colorful anecdotes along the way.